Light Dragoons : the Making of a Regiment. - Mallinson, Allan (Pen and Sword, 2012)
Although only formed in December 1992, The Light Dragoons look back to a history that began in the days of the first Jacobite rebellion. In 1922 a reduction in the Army's strength saw the amalgamation of four regiments of Hussars into the 13th/18th Hussars and the 15th/19th Hussars. Now they too have been amalgamated, with a name that reverts to the titles of the four original regiments in the eighteenth century. Allan Mallinson, the novelist and a former commanding officer of the 13th/18th Hussars, not only follows with admirable clarity and dexterity the fortunes of The Light Dragoons' prede.